Return to education in Malaysia. - Said, Rusmawati; Haris, Asmaddy; Mc.Nabb, Robert (Universiti Utara Malaysia, 2009)
The aim of this paper is to present a picture of return to education in Malaysia over the period from 1984 to 1997 based on earning equations model. The paper employed a set of data comprising micro-level data from the Household Income Survey (HIS) for several years during the period 1984 to 1997. The main fi nding of this paper is the changes in the wage diff erentials favouring the middle level of education (secondary level of education) workers. In general, the results show that the return for each level of qualifi cation declined between 1984 and 1997, especially at the higher levels (diploma and degree). Interestingly, the return to education for females at low levels of education is higher than the return by males. However, at higher levels of qualifi cation, especially for those with secondary and high school qualifi cations, males traditionally have a higher return compared to females workers. The results also indicated a significant gender diff erential, however the diff erences has fallen over time.